(3CSGSjGJ fXe GdeYdheGJ GdEOGQjIs - (3YdGA(B, (3GdSGdejs; (3gdGd GdHjGJj(B, s ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2009)
(3jVe GdeYdheGJ hGdEOGQI, GdfXGe, fXe GdeYdheGJ GdEOGQjI, efgLjI JWhjQ fXe GdeYdheGJ GdEOGQjI, caGAI COGA fXe GdeYdheGJ GdEOGQjI, JWhjQ fXe GdeYdheGJ GdEOGQjI hCfhGYgG, fXe GdeYdheGJ GdhXjajI, EOGQI fXe GdeYdheGJ GdEOGQjIs
(3HjHdjhZQGajG(B: (3U U(B.289-292s
Keywords: (3GdEOGQIs; (3GdEOGQI HGdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s